An antioxidant activity of Cinnamonum tamala improves histopathological alterations and biochemical parameters in alloxan induced diabetic rats - Pochhi, Mamata Laxmikant (Asian Journal of Medical Sciences, 2019)
Background: Diabetic mellitus is a multifactorial disorder associated with its devastating consequences has assumed epidemic proportion. Diabetes mellitus (DM) is a global health problem and the incidence of DM is increasing at alarming rate all over the world. Many Indian medicinal plants have been reported to possess potential antidiabetic activity and could play important role in the management of diabetes with less adverse effects. Aims and Objectives: The main objective of this study was to focus on the anti-diabetic activity of Cinnamomum tamala, with special reference to its curative and protective role in alloxan induced diabetic rats. Attempts were further made to study the antioxidant properties of C. tamala leaves. Materials and Methods: The diabetic rats were administered orally with the aqueous leaves extracts of Cinnamonum tamala (250 mg/kg) for 30 days. The results were compared with standard drug Tolbutamide. Result: The alloxan treated diabetic control rats showed a significant increase in the plasma glucose, glycosylated hemoglobin (HbA1C), glucose-6-phosphatase, aldolase, LDH, ALT, AST, ALP and GGT activity, free radicals formation with a concomitant decrease in glycogen content in the liver and serum insulin level and phosphoglucoisomerase and hexokinase activity in tissues as compared to normal control rats. Oral administration of C. tamala extract for 30 days showed significant result as compared to Tolbutamide and diabetic control rats. Conclusion: On the basis of above findings it can be concluded that extracts of C. tamala to alloxan induced diabetic rats showed significant positive changes in the biochemical and histopathological parameters related to carbohydrate and protein metabolism.